Economic and political transitions from premodern to modern states in the Meiji Restoration and Xinhai Revolution: A strategic approach - Masahiko Aoki (Asian Development Bank Institute (ADBI), 2014)
Economists often identify a reduction in the share of agricultural employment as a quantitative indication of the economic growth of nations. But this process did not occur in earnest in the People's Republic of China until the 1980s and to some extent in Japan until well into the mid-20th century. Were extractive political regimes, commonly regarded as the primary drivers of economic performance, solely responsible for the lateness of these developments? This paper deals with this question from a strategic perspective by examining the interactions between the polity and the economy in both countries. It begins by characterizing the complementary nature of the peasant-based economy and the agrarian-tax state in premodern China and Japan. It then describes how endogenous strategic forces evolved from among the intermediate organizations in each country to challenge the incumbent dynastic ruler in response to the commercialization of the peasant-based economy on one hand and the fiscal and military weakening of the agrarian-tax state on the other. The paper then introduces a three-person game model between a ruler and two challenging organizations, and derives conditions for multiple equilbria and their comparative static. The analytical results help to identify the endogenous strategic forces that led the Meiji Restoration and the Xinhai Revolution to move from a premodern state of play to nation-state building and modern economic regimes in each country.
Keywords: B52; C72; N40; N45; O10; P51; 330; endogenous institutional change; institutional complementarity; Chinese economy; Meiji Restoration; tax state; peasant-based economy; three person politico-economic game